2022
DOI: 10.3390/jcm11040905
|View full text |Cite
|
Sign up to set email alerts
|

Remote Assessment of Quality of Life and Functional Exercise Capacity in a Cohort of COVID-19 Patients One Year after Hospitalization (TELECOVID)

Abstract: Studies have reported persistent symptoms in patients hospitalized for COVID-19 up to 6 months post-discharge; however, sequalae beyond 6 months are unknown. This study aimed to investigate the clinical status of COVID-19 patients one year after hospital discharge and describe the factors related to poor outcomes. We conducted a single-center, prospective, cohort study of patients in Le Havre hospital (France) between 1 March 2020 and 11 May 2020. Baseline characteristics were collected from medical charts (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…CFS-based frailty predicted late mortality more strongly than the severity of COVID-19 [ 164 ]. Frailty was also associated with poor mental health [ 165 ], poor exercise capacity [ 166 ], reduced quality of life [ 167 ], and sustained symptom of COVID-19 [ 168 ]. Conversely, COVID-19 is reported to increase the risk of frailty [ 169 172 ].…”
Section: Effects Of Age and Sex On Long Covidmentioning
confidence: 99%
“…CFS-based frailty predicted late mortality more strongly than the severity of COVID-19 [ 164 ]. Frailty was also associated with poor mental health [ 165 ], poor exercise capacity [ 166 ], reduced quality of life [ 167 ], and sustained symptom of COVID-19 [ 168 ]. Conversely, COVID-19 is reported to increase the risk of frailty [ 169 172 ].…”
Section: Effects Of Age and Sex On Long Covidmentioning
confidence: 99%
“…These findings are consistent with those of previous studies. [16][17][18][19] Moreover, our analyses showed that admission was associated with increased functional limitations and/or mortality after discharge. Previous studies described functional impairments following ICU admission owing to COVID-19 and other critical illnesses.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, Combret et al. 31 ) reported that frailty at admission is associated with low MCS scores 1 year after hospitalization for COVID-19. The inclusion of patients limited to those under the age of 75 years who were independent in ADL before admission, along with the lower proportion of females, may have influenced the results in this study.…”
Section: Discussionmentioning
confidence: 99%
“…28,29) In a study of COVID-19 patients with sequelae lasting more than 4 weeks after onset, Poudel et al 30) reported that being female was a significant determinant associated with an MCS score below 50 on the SF-36. In addition, Combret et al 31) reported that frailty at admission is associated with low MCS scores 1 year after hospitalization for COVID-19. The inclusion of patients limited to those under the age of 75 years who were independent in ADL before admission, along with the lower proportion of females, may have influenced the results in this study.…”
Section: Discussionmentioning
confidence: 99%